Safety of Allogeneic Umbilical Cord Blood Stem Cells Therapy in Patients with Severe Cerebral Palsy: A Retrospective Study - Mei Feng; Aili Lu; Hongxia Gao; Caiwen Qian; Jun Zhang; Tongxiang Lin; Yuanqi Zhao (Hindawi Limited, 2015)
This retrospective study aimed to assess the safety of patients with severe cerebral palsy (CP), who received allogeneic umbilical cord blood stem cells (UCBSCs) treatment from August 2009 to December 2012 in Guangdong Provincial Hospital of Chinese Medicine. A total of 47 patients with average age of 5.85±6.12 years were evaluated in this study. There was no significant association with allogeneic UCBSCs treatments found in the data of the laboratory index . No casualties occurred. Some adverse events during treatments were found in 26 (55.3%) patients, including fever (42.6%) and vomiting (21.2%). Intrathecal infusion and the ages at the initiation of treatment (≤10 years old) were risk factors for the occurrence of adverse events by logistic regression analysis. However, all adverse events disappeared after symptomatic treatment. No treatment related serious adverse events were found in follow-up visits within 6 months. In conclusion, allogeneic UCBSCs treatment was relatively safe for severe CP patients.